A Celebration of Health Literacy Month at State University of Ceara, Brazil. Issue 3 (3rd July 2018) - Sampaio, Helena Alves de Carvalho; Sampaio Lima, Patrícia Paula de Carvalho; Arruda, Soraia Pinheiro Machado; Vergara, Clarice Maria Araújo Chagas
Abstract: The aim of this article is to describe the activities performed during the health literacy month commemoration at the State University of Ceara, Brazil, during its University Week Events 2015–2017, and to reflect about successes, failures and perspectives from these events. The events focused on five major points: defining health literacy; describing assessments and measurements of health literacy; the importance of health literacy on professional practice; when the principles of health literacy should be practiced; and the significance of October as Health Literacy month. The Teach-Back method of communication was introduced, which not only serves as the initial step in starting the discussion on the importance of health literacy for patient empowerment during patient-clinician encounters, but also to assist institutions in developing pathways towards becoming health literate organizations.